2022
DOI: 10.7759/cureus.21457
|View full text |Cite
|
Sign up to set email alerts
|

Arrhythmogenic Right Ventricular Cardiomyopathy in a Patient Experiencing Out-of-Hospital Ventricular Fibrillation Arrest Twice: Case Report and Review of the Literature

Abstract: We present a case of a 62-year-old male who was admitted to the hospital with out-of-hospital ventricular fibrillation (VF) arrest. He had a VF arrest in 2011 and was admitted to another hospital. He had several investigations excluding cardiac magnetic resonance imaging, all of which were normal. He was playing tennis on both occasions when he experienced the VF arrest. His electrocardiogram on admission showed AF with partial right bundle branch block, inverted T waves in V1-V2, low voltage QRS complexes, ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The clinical findings and morphological features of the disease support the non-ischaemic atrophy of the right ventricular myocardium rather than the congenital absence of the myocardium that leads to arrhythmias in adolescents and young adults [ 6 , 7 ]. AVC is the second leading cause of death in young patients following hypertrophic cardiomyopathy [ 1 ]. Thiene et al (1988) reported autopsy findings suggestive of AVC in a series of cases of exertional sudden cardiac deaths in young adults; the ECGs in these patients demonstrated right precordial leads with negative T waves and left bundle branch (LBBB) morphology type ventricular arrhythmia [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The clinical findings and morphological features of the disease support the non-ischaemic atrophy of the right ventricular myocardium rather than the congenital absence of the myocardium that leads to arrhythmias in adolescents and young adults [ 6 , 7 ]. AVC is the second leading cause of death in young patients following hypertrophic cardiomyopathy [ 1 ]. Thiene et al (1988) reported autopsy findings suggestive of AVC in a series of cases of exertional sudden cardiac deaths in young adults; the ECGs in these patients demonstrated right precordial leads with negative T waves and left bundle branch (LBBB) morphology type ventricular arrhythmia [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Khan et al (2022) reported a case of a 62-year-old patient who had two out-of-hospital cardiac arrests in a span of a decade and was successfully resuscitated both times. His coronary arteries were unobstructed and CMR findings were suggestive of ARVC, for which he had an ICD implanted for primary prevention [ 1 ]. Latt et al (2017) published a case report of a 33-year-old male athlete presenting with palpitations and chest pain, on a background of similar episodes five years previously [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations